Analysis of Student Satisfaction Level Towards Matriculation Teachers in Chemistry and Management Study Program of Tribuana Kalabahi University - Eunike Molebila; Alboin Selly; Halena Muna Bekata; Yessy Mata; Jon Abraham Lalang Yame; Triznawasti Yudita Daik; Petrus Mau Tellu Dony (Jurnal Inovasi Pendidikan dan Sains, 2024)
The matriculation program at Tribuana Kalabahi University aims to help new students adapt to the academic environment through effective initial teaching. However, to ensure that this program runs according to students' expectations, a comprehensive eval_uation of the quality of teaching is needed. This study aims to eval_uate the satisfaction of new students of the Chemistry and Management Study Programs with matriculation teaching based on aspects of teaching quality, methods, and lecturer-student interaction. Using a quantitative approach, data were collected through a closed questionnaire on a Likert scale of 1-5 distributed to 59 matriculation students. Data analysis using descriptive statistics showed that 87.64% of Chemistry Study Program students and 90.53% of Management Study Program students were satisfied to very satisfied with the teaching provided. Based on the existing assessment criteria, this level of satisfaction places the quality of teaching in the very good category, although there were 11.72% and 9.45% of students in each study program who were quite satisfied, indicating room for improvement. In conclusion, matriculation teaching in both study programs has met students' expectations with a high level of satisfaction, but efforts to improve quality are still needed to achieve more optimal results